Programação térmica fetal: efeitos sobre a temperatura de preferência e características morfofisiológicas de frangos de corte - Morita, Viviane de Souza [UNESP] (2015)
Heat stress changes the performance and morphological and functional characteristics of broilers. Thermal programming during fetal development has been shown to be effective in the induction of adaptive characteristics to heat, increasing the thermotolerance of the birds during the post-hatching period by epigenetic adaptation. This study examined the effects of exposure to cold or hot incubation temperature during the fetal stage on the physical and physiological characteristics of chicks, at hatching, and chickens reared under preferred, recommended or high temperature. In Chapter 1 we present a theoretical approach to the topic. In Chapter 2, the effects of cold or hot temperature during the fetal stage on incubation parameters (temperature, eggshell and hatchability), preferred ambient temperature and characteristics of newly hatched chicks (body and organs weight, skin and feathering characteristics, body surface and rectal temperature and plasma T3, T4 and GH concentrations) were examined. For this, hatching eggs from a commercial broiler breeder flock (Cobb 500®) were exposed from day 13 of incubation to cold (36°C), control (37.5°C) or hot (39°C) temperature. The data show that exposure to cold reduced body surface temperature, skin vascularity and plasma T3 and GH concentrations. Moreover, exposure to hot increased eggs hatchability, body surface temperature and dermal vascularity, reduced skin thickness and increased thermal preference of the chicks. In Chapter 3 was studied whether exposure to cold or hot incubation temperature alters preferred ambient temperature and response to heat stress of broilers along rearing phase. For this, we adopted the same incubation protocol used in Chapter 1. After hatching, the birds were housed in climatic chamber with temperature set to the recommended values for the line. Weekly, during the six weeks of rearing, thermal preference and response to heat stress of birds were ...